The use and perceived benefits resulting from the use of complementary and alternative medicine by cancer patients in Australia - Oh, B.; Butow, P.; Mullan, Barbara; Beale, P.; Pavlakis, N.; Rosenthal, D.; Clarke, S. (Wiley-Blackwell Publishing Ltd., 2010)
Aim: The use of complementary and alternative medicine (CAM) by cancer patients is growing. However, few studies have examined the perceived benefits and adverse effects resulting from the use of CAM by cancer patients. The aim of this study was to evaluate CAM use by cancer patients and to explore their perceptions of the benefit, safety and efficacy of CAM in general. Methods: Oncologists from three university teaching hospitals screened patients for eligibility. Eligible patients (N = 1323) were mailed a letter of invitation with a questionnaire between January and May 2008. Results: Overall 381 questionnaires were returned, showing that 65% of cancer patients used at least one form of CAM. Patients considered taking biological CAM before, during and after chemotherapy. Up to 90% of CAM users believed that CAM provided potential health benefits and less than 3% reported adverse effects experienced from the use of CAM. Most respondents (80%) believed CAM can provide health benefits even when efficacy has not been proven. Most patients (90%) believed that doctors should consider learning about CAM to provide appropriate advice to their cancer patients, and most (83%) indicated they would be happier to accept CAM if it was offered by the hospital. Conclusion: A substantial portion of Australian cancer patients use CAM. Given the limited data on efficacy and safety for most CAM, it may be reasonable to offer CAM within the hospital environment so its use can be monitored and patients can receive more evidence-based care.